Role of apoptosis repressor with caspase recruitment domain (ARC) in cancer - Yu, Zhongjie (Oncol Lett, 2019)
Apoptosis repressor with caspase recruitment domain (ARC) is a potent inhibitor of apoptosis. Under physiological conditions, ARC is abundantly expressed in terminally differentiated cells, including cardiomyocytes, skeletal muscles and neurons. ARC serves a key role in determining cell fate, and abnormal ARC expression has been demonstrated to be associated with abnormal cell growth. Previous studies have revealed that ARC was upregulated in several different types of solid tumor, where it suppressed tumor cell apoptosis. Furthermore, the increased expression levels of ARC in cancer cells contributed to the development of therapeutic resistance and adverse clinical outcomes in patients with leukemia. However, the exact role of ARC, as well as the underlying molecular mechanisms involved, remain poorly understood. The present review summarizes the characteristics of ARC and its cytoprotective role under different conditions and describes the potential ARC as a new target for cancer therapy.